RAPD analysis of somadonal variation in banana (Musa acuminate L.) cultivar Valery - Sheidai, Masoud (Acta Biologica Szegediensis, 2008)
Thirty decamer RAPD primers were used to study somaclonal variation among the parental plants as well as regenerated plants of the first, third, fifth, seventh and ninth sub-cultures. Eighteen out of thirty primers produced 289 bands in all the genotypes studied. Hundred and forty-two bands (48.95%) were common in the parental genotype and the regenerated plants while 147 bands were polymorph (51.40%). Among the primers used, OPI-07 produced the highest number of bands (24) while primers OPH-16 produced the lowest number (5). In total 74 specific bands were observed in the parental genotype and the regenerated plants of the sub-cultures. The presence of specific band/loci in the parental plants and loss of it in the regenerated plants of different sub-cultures indicates the loss of certain loci during tissue culture due to somaclonal variation. Such specific loci are of high importance in the genetic identification of the genotypes or somaclones from each other. Grouping of the parental cultivar and their sub-cultures regenerated plants indicate the genetic distinctness of the genotypes studied as they are placed in different clusters/groups far from each other. It also seems that the genetic variations induced in the regenerated plants increase with the time-period of the sub-culture.